Hungary : Technical Assistance Report-Operational Aspects of Establishing an Asset Management Company. (IMF Staff Country Reports; Country Report ;, 2015)
This Technical Assistance report highlights that the Hungarian economy is recovering gradually from a sharp recession. Restoring credit growth has become a central policy objective, seen as key to economic recovery and effective monetary transmission. Recent legislation significantly affects the banking sector. The Settlement Act requires banks to compensate borrowers for 'unfair lending practices' on a retroactive basis for past unilateral contract modification and for the use of bid-ask spreads in calculating foreign currency loan disbursements. The principle areas of concern include the institutional factors and financial issues shown in the text table. The rest of this report discusses ways of mitigating the risks stemming from these factors, through setting appropriate objectives and institutional arrangements, and good operational practices. A clear mandate and well-defined objectives are critical for the effective functioning of asset management companies (AMC). Regardless of the ultimate policy objective behind the establishment of AMCs, once established, the institution should focus single minded on maximizing the value of the assets it has acquired.